O Projeto de uma instituição pública de longa permanência para idosos em Belém - SILVA, Nelma Renata da (2023)
To Promote the debate involving the aging of the brazilian population and how society should get ready for this “event” which is already happening. It briefly tells the history of the formation of the long term care Institution for the elderly. It checks and discusses whether the legislation and rules in force regarding the long term care Institution for the elderly apply to the real needs of this public or if there is the possibility of adding, adapting or amendment of these instruments, based on the reports obtained during technical visits and on the public services offered around the shelter location. The work is developed for the construction of the architectural project of a long-term care institution for the elderly in the city of Belém, which seeks to cover as much as possible the needs of the elderly and the workers who will stay there, following the indications of NBR9050 and providing them dignity, comfort and security during the elderly period.